Analysis of the Correlations of Marketing Mix with Purchasement of Teh Sardines ABC at Kota Pontianak - Sapurdi, Sapurdi; Aritonang, Marisi; Imelda, Imelda (Jurnal Sains Mahasiswa Pertanian, 2018)
This research aimed to find out the correlations of marketing mix (product, price, promotion, and place) to the purchasing decision of Sardies ABC at Kota Pontianak. Research locations selected by deliberately in Kota Pontianak with the consideration that this area is the industrial and marketing center.This research method is survey by using Rank Spearman (Rs) correlation analysis.The results show that showedthat product priceand place of the marketing mix have high correlation while promotion component have not correlation over consumer decisions in purchasing of Sardies ABC at Kota Pontianak.